Geospatial Intelligence (GEOINT) As A National Defense Strategy for Information Overload in Indonesia - Muhammad Aldin Yusfan; Asep Adang Supriyadi; Sukendra Martha; Rudi Agus Gumilang Gultom; Sri Kartika Sakti (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2021)
The global phenomenon in the Industrial Revolution 4.0 era is currently hitting Indonesia. Many information floods the public every minute with various content spread across multiple media. This information for a country can be a powerful weapon as a form of intelligence product to prepare a national defense strategy. The demands of an increasingly fast-paced era make GEOINT needed to obtain information quickly, accurately and integrate synthesis and analysis. Therefore, this study was conducted to identify the development of GEOINT in Indonesia and its application in overcoming information overload in the present. This study uses the library method by collecting references relevant to the research problem from various sources. The study results indicate that the overload of information from multiple increasingly sophisticated media due to technological developments has made GEOINT's information sources richer. GEOINT in Indonesia continues to optimize accuracy and speed in geospatial analysis to avoid losing to the rate of data sources that continue to increase, both from human resources, hardware, software, and access to information available according to Indonesia's needs. GEOINT as a national defense strategy can be carried out as a form of effective information collection and can protect confidential information. GEOINT will become increasingly valuable in both military and non-military management over the next few years.